Two new species of the genus Glenea Newman, 1842 (Coleoptera: Cerambycidae: Lamiinae: Saperdini) from Mindanao and Luzon Islands Philippines - Medina, Milton Norman; Cabras, Analyn A.; Dam, Matthew H. Van (Zootaxa, 2023)
We describe and illustrate two new species of Glenea Newman, 1842 from the Philippines: G. barsevskisi sp. nov. and G. vitali sp. nov. Both species belong to the subgenus Glenea sçnsű strictô. At present, the total number of Glenea species in the Philippines is 89 (79 species and 10 subspecies).